Tea catechin and caffeine activate brown adipose tissue and increase cold-induced thermogenic capacity in humans - Yoneshiro, Takeshi; Matsushita, Mami; Hibi, Masanobu; Tone, Hiroshi; Takeshita, Masao; Yasunaga, Koichi; Katsuragi, Yoshihisa; Kameya, Toshimitsu; Sugie, Hiroki; Saito, Masayuki (The American journal of clinical nutrition, 2017)
ABSTRACT Background: The thermogenic effects of green tea catechin have been repeatedly reported, but their mechanisms are poorly understood. Objective: The aim of this study was to investigate the acute and chronic effects of catechin on brown adipose tissue (BAT), a site specialized for nonshivering thermogenesis, in humans. Design: Fifteen healthy male volunteers underwent fluorodeoxyglucose-positron emission tomography to assess BAT activity. To examine the acute catechin effect, whole-body energy expenditure (EE) after a single oral ingestion of a beverage containing 615 mg catechin and 77 mg caffeine (catechin beverage) was measured. Next, to investigate the chronic catechin effects, 10 men with low BAT activity were enrolled. Before and after ingestion of the catechin beverage 2 times/d for 5 wk, cold-induced thermogenesis (CIT) after 2 h of cold exposure at 19°C, which is proportional to BAT activity, was examined. Both the acute and chronic trials were single-blinded, randomized, placebo-controlled, season-matched crossover studies. Results: A single ingestion of the catechin beverage increased EE in 9 subjects who had metabolically active BAT (mean ± SEM: +15.24 ± 1.48 kcal, P < 0.01) but not in 6 subjects who had negligible activities (mean ± SEM: +3.42 ± 2.68 kcal). The ingestion of a placebo beverage containing 82 mg caffeine produced a smaller and comparative EE response in the 2 subject groups. Multivariate regression analysis revealed a significant interaction between BAT and catechin on EE (β = 0.496, P = 0.003). Daily ingestion of the catechin beverage elevated mean ± SEM CIT (from 92.0 ± 26.5 to 197.9 ± 27.7 kcal/d; P = 0.009), whereas the placebo beverage did not change it. Conclusion: Orally ingested tea catechin with caffeine acutely increases EE associated with increased BAT activity and chronically elevates nonshivering CIT, probably because of the recruitment of BAT, in humans. These trials were registered at www.umin.ac.jp/ctr/ as UMIN000016361.